Work-related musculoskeletal symptoms and coping strategies among dental auxiliaries at hospital universiti Sains Malaysia - Normastura Abd Rahman; Munirah Mohd Adnan; Azizah Yusoff; Joel Moh Heng Shu; Khadijah Rustam (Wolters Kluwer Medknow Publications, 2020)
Background: Dental personnel are vulnerable to work-related musculoskeletal symptoms (WMSS) due to the nature of their profession. Aim: To determine WMSS experienced by dental auxiliaries and their coping strategies toward these symptoms. Setting and Design: A cross-sectional study was conducted on 82 dental auxiliaries at a university dental hospital in Malaysia. Materials and Methods: Nordic musculoskeletal questionnaire and the Brief COPE questionnaire were used to measure the musculoskeletal symptoms and coping strategies of the respondents, respectively. Data were analyzed using IBM SPSS version 22.0. Results: Dental auxiliaries consisted of dental staff nurses (30.5%), dental surgery assistants (40.2%), dental technologists (18.3%), and healthcare assistants (11.0%). Their mean [standard deviation (SD)] age was 33.4 (7.60) years. Most of the respondents had been troubled with ache, pain, and discomfort at the neck, 54.9% (95% confidence interval 44.0%, 66.0%]. In addition, they were troubled mainly with distress at the low back (34.1%) and the ankle or feet (34.1%) which had prevented the respondents from doing their regular job over the past 12 months. The most common areas that had troubled the respondents over the past 7 days were the neck (36.6%), low back (36.6%), and ankle or feet (36.6%). The coping strategy most commonly practiced by the respondents was religion with a mean (SD) score of 3.70 (2.15), followed by active coping [3.13 (0.68)] and acceptance [3.13 (0.69)]. Conclusion: The prevalence of WMSS was high in the dental auxiliaries particularly in the neck region. The most common coping strategy used was religion. Awareness programs on the prevention of WMSS among the dental auxiliaries should be increased.